Effects of sulfurization temperature on structural, morphological, and optoelectronic properties of CTS thin films solar cells - Hossain E.S.; Chelvanathan P.; Shahahmadi S.A.; Ferdaous M.T.; Bais B.; Tiong S.K.; Amin N. (S.C. Virtual Company of Phisics S.R.L, 2023)
Cu2 SnS3 (CTS) thin films were fabricated by two-step process: deposition of precursor by RF magnetron sputtering, and subsequent sulfurization at different temperatures. The influence of sulfurization temperatures on the structural, morphological, optical, and electrical properties was investigated to find out the optimum growth route for CTS formation kinetics. All prepared samples were found Sn-rich by the EDX compositional analysis. Structural analysis confirmed the CTS formation with the impurity phase of Cu4 Sn7 S16 at lower temperature, and Sn2 S3 at higher sulfurization temperature. Crystallite size of these films was found to increase from 53.2 to 61.3 nm with increasing the sulfurization temperatures from 520 to 580 C. The same trend was also observed for the grain size in the morphological analysis. Bandgap was varied from 0.87 to 0.92 eV, as the sulfurization temperature increased from 520 to 580 C. Carrier concentration was found to decline with increasing sulfurization temperature while mobility and resistivity showed a progressive increment at higher temperatures. 2018, S.C. Virtual Company of Phisics S.R.L. All rights reserved.